"A Refugee from Belief": Agha Shahid Ali's Poetics of Rupture. (3rd January 2023) - Dutta, Upasana
Abstract: This article attempts a reassessment of the political aspirations within Agha Shahid Ali's poetics through a close reading of The Country without a Post Office. Although Shahid's formal innovations have often been prioritized over his political commitments within scholarly evaluations of his work, I contend that in this collection, Agha Shahid Ali practices a "poetics of rupture": holding themes of coherence and disruption, continuity and breakage, the global and the local in sustained tension with each other throughout the volume. Forged through a political commitment to represent Kashmir in crisis, his poetics of rupture is simultaneously formally founded on breakage and discontinuity, and itself ruptures, as I eventually propose, the very binaries (poetics versus polemics, personal versus political, local versus global) that shadow political poetry. I demonstrate the specifics of Shahid's poetics of rupture through an analysis of his work with literary allusions and poetic forms. Eventually, this article contends that recognizing the political import of his poetics of rupture has consequences for our recognition of the crisis in Kashmir itself and the ethical and formal possibilities surrounding the representation of this crisis.